SISTEM INFORMASI PEMESANAN BAJU PADA TOKO FANI HOUSE BERBASIS WEB MOBILE - Ratna Anugraheni, Sri Lestari; Khristianto, Teguh (Information Technology and Telematics, 2018)
Abstract - Fani House is a business engaged in the sale of women's clothing. Various models and motifs of clothing are available at Fani House, not only clothes, Fani house also sells various kinds of women's fashion such as pants, jackets, outer, t-shirts, bags and much more. So the authors want to design and build an information system for ordering mobile web-based clothes at the Fani House Clothing Store that can be accessed via the website or through a browser on a mobile phone (smartphone) so that orders can be made effectively and efficiently. The software used in making this mobile website uses PHP and MySQL. The results of this study can be concluded that makes it easy to search information and can be accessed 24 hours megenai products sold in Semarang Fani House Shop and make it easier in terms of ordering. An additional feature of this website is to search for clothes based on the size of the shirt.